The influence of zero-value subtraction on the performance of two laser fluorescence devices for detecting occlusal caries in - Rodrigues, Jonas de A.; Hug, Isabel; Diniz, Michele B. [UNESP]; Cordeiro, Rita C. L. [UNESP]; Lussi, Adrian (Amer Dental Assoc, 2008)
Background. The aim of this study was to evaluate the influence of zero-value subtraction on the performance of two laser fluorescence (LF) devices developed to 'detect occlusal caries.Methods. The authors selected 119 permanent molars. Two examiners assessed three areas (cuspal, middle and cervical) of both mesial and distal portions of the buccal surface and one occlusal site using an LF device and an LF pen. For each tooth, the authors subtracted the value measured in the cuspal, middle and cervical areas in the buccal surface from the value measured in the respective occlusal site.Results. The authors observed differences among the readings for both devices in the cuspal, middle and cervical areas in the buccal surface as well as differences for both devices with and without the zero-value subtraction in the occlusal surface. When the authors did not perform the zero-value subtraction, they found statistically significant differences for sensitivity and accuracy far the LF device. When this was done with the LF pen, specificity increased and sensitivity decreased significantly.Conclusions. For the LF device, the zero-value subtraction decreased the sensitivity. For this reason, the authors concluded that clinicians can obtain measures with the LF device effectively without using zero-value subtraction. For the LF pen, however, the absence of the zero-value subtraction changed both the Sensitivity and specificity, and so the authors concluded that clinicians should not eliminate this step from the procedure.Clinical Implications. When using the LF device, clinicians might not need to perform the zero-value subtraction; however, for the LF pen, clinicians should do so.
Keywords: occlusal caries; DIAGNOdent 2095; DIAGNOdent pen 2190; laser fluorescence; zero value